(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2009)
The primary objective of anaesthesia is to facilitate surgery at minimal risk to the patient and to ensure safe optimal recovery following the procedure. The minimal risk to the neurosurgical patient can be achieved with meticulous attention to the detail of intraoperative systemic and brain homeostasis. Safe early recovery from craniotomy necessitates an anaesthetic technique pharmacology adequate to permit early awakening. The present study was designed to observe the effect of different anaesthetic technique that permits early recovery and hemodynamic stability. A total number of thirty patients both male and female age range 18 to 60 yrs having ASA grade-I & II and were randomly selected. They were equally divided into two groups. Group A received TPS infusion and group B received isoflurane inhalation with low dose of TPS infusion. Other drugs remained same for both group. Group A Received induction dose of TPS 4 - 5 mg/kg, maintained by TPS (4 - 5 mg/kg/h infusion), fentanyl (3 mgm/kg bolus, 1 - 2 mgm/ kg/h infusion), oxygen/N2O mixture FiO2 being 0.3. Group B- Received induction dose of TPS 4 - 5 mg/kg and maintained by isoflurane 0.5%, oxygen/ N2O mixture FiO2 being 0.3, fentanyl (3 mgm/kg bolus, 1 - 2 mgm/kg/h infusion), and low dose TPS (1 - 2 mg/kg/h) infusion. In all patients induction was done with TPS 4 - 5 mg/kg and vecuronium (0.1 mg/kg) was used for tracheal intubation, muscle relaxation was maintained by vecuronium 0.01 mg/kg intermittently. Both groups received midazolam (0.1 mg/kg), lignocaine 1.5 mg/kg 2 minutes before induction. Both groups received frusemide 1 mg/ kg just after induction and mannitol 1 gm/kg when scalp incision was given. Anaesthetic procedure was performed with monitoring of hemodynamic variable pulse, blood pressure, SPO2, ETCO2, temperature, urine output. Hemodynamic variable pulse, blood pressure were measure before induction, at intubation, every 15 min. interval and before extubation. Data were analyzed by paired and unpaired student’s t-test as appropriate using SPSS software. Hemodynamic response to intubation does not differ significantly between the two groups. But it was observed that at intubation in both groups the pulse and mean arterial blood pressure was raised in compare to baseline, which gradually came down as anaesthetic depth increased and then remained stable all through the procedure. Recovery was evaluated using Aldrete score. Total score significantly differ between two groups up to 30 min after extubation. Group A showed delay recovery up to 30 min in compare to group B. But after 30 min there was no significant difference in scoring between two groups. Total cost of main anaesthetic agent used significantly lower in group A. This study showed that the total infusion of TPS technique was as equally effective as using low concentration of isoflurane with conjunction of low dose TPS regarding perioperative hemodynamic stability. But the cost was minimal in thiopental sodium infusion group with the expense of a little bit delayed recovery. Journal of BSA, Vol. 21, No. 1, January 2008 21-28